Math, asked by atharvabhatkoorse50, 6 hours ago

Pls solve this problem and send the solution I need the steps also ​

Attachments:

Answers

Answered by Anonymous
2

 \frac{x - 1}{3}  +   \frac{y + 2}{2} = 3 \\  \\  \frac{2(x - 1) + 3(y + 2)}{6}   = 3 \\  \\  \frac{2x - 2 + 3y + 6}{6}  = 3 \\  \\  \frac{2x + 3y + 4}{6}  = 3 \\  \\ 2x + 3y + 4 = 6 \times 3 \\  \\ 2x + 3y + 4 = 18 \\  \\ 2x + 3y = 18 - 4 \\  \\ 2x + 3y = 14. \:  \:  \:  \: ....(i)

 \frac{1 - x}{6}  -   \frac{y - 4}{2}  =  \frac{1}{2}   \\  \\  \frac{1 - x - 3(y - 4)}{6}  =  \frac{1}{2}  \\  \\ 2(1 - x - 3y + 12) = 6 \\  \\ 2 - 2x -6 y + 24 = 6 \\  \\  - 2x - 6y + 26 = 6 \\  \\  - 2x - 6y = 6 - 26 \\  \\  - 2x - 6y =  - 20 \\  \\ - ( 2x + 6y) =  - 20 \\  \\ 2x + 6y = 20 \:  \:  \: ....(ii)

from \: equation \: (i) \\  \\ 2x + 3y = 14 \\  \\ 2x = 14 - 3y \\  \\ x =  \frac{14 - 3y}{2} \\  \\ substitute  \: \: the  \: \: value \:  \: of \:  \: x \:  \: in \: \:  equation \: (ii) \\  \\ 2x + 6y = 20 \\  \\ 2( \frac{14 - 3y}{2} ) + 6y = 20 \\  \\  \frac{28 - 6y}{2}  + 6y = 20 \\  \\  \frac{28 - 6y + 12y}{2}  = 20 \\  \\ 28  + 6y = 40 \\  \\ 6y = 40 - 28 \\  \\ 6y = 12 \\  \\ y =  \frac{12}{6}  \\  \\ y = 2. \\  \\ now \:  \: substitute \:  \: the \: value \:  \: of \:  \: y \:  \: in \:  \: equation \:  \: (i) \\  \\ 2x + 3y = 14 \\  \\ 2x + 3 \times 2 = 14 \\  \\ 2x + 6 = 14 \\  \\ 2x = 14 - 6 \\  \\ 2x = 8 \\  \\ x =  \frac{8}{2}  \\  \\ x = 4.

 so \: \:  the \:  \: value \:  \: of \:  \: x = 4 \:  \: and \:  \: y = 2.

Answered by juwairiyahimran18
1

see abv attachment .. !!

x = 4 and y = 2.

Similar questions